On the detailed design of a quasi-zero stiffness device to assist in the realisation of a translational Lanchester damper. (1st February 2022) - Gatti, G.; Shaw, A.D.; Gonçalves, P.J.P.; Brennan, M.J.
Graphical abstract: Highlights: A prototype translational Lanchester damper is studied, designed and tested. A quasi-zero stiffness suspension is proposed and added in parallel to the damper. Despite inherent nonlinearity, linear-like behaviour is observed. Design guidelines are provided for a true quasi-zero stiffness suspension. Abstract: A translational Lanchester damper is a device that adds damping to a structure at a point using a series combination of a viscous damper and a mass. The problem in the practical realisation of such a device is that a stiffness is required to support the mass, which changes the dynamic behaviour of the device, introducing a resonance frequency due to the interaction of the stiffness and inertia forces. This is a dynamic vibration absorber. To achieve a device that behaves broadly as a Lanchester damper rather than a dynamic vibration absorber, a very low stiffness is required, and this is the focus of this paper. The low stiffness is realised using a combination of linear springs and rigid links arranged with specific geometry into a compact device. Although the geometric configuration of the components leads to an inherently nonlinear device, the aim is to limit its working condition and exploit the linear-like behaviour. To this end, how the geometry affects the nonlinear behaviour is studied in detail, providing general guidelines for its design. A prototype Lanchester damper incorporating the low stiffness element was manufactured and tested on a single mode and two multi-modal vibrating structures.